PKM PENGENALAN UU DESA: LANGKAH PEMERINTAH MENGGENAPI IKRAR KESEJAHTERAAN MELALUI PEMBENTUKAN PERATURASN DESA (PERDES) DI DESA WANAHERANG GUNUNG PUTRI BOGOR - Didik Suhariyanto (Jurnal Abdimas Bina Bangsa, 2023)
Village potential needs to be developed for village development and determined by Village Regulations (Perdes). The potential that exists in the potential village is Natural Resources (SDA) and Human Resources (HR) as well as facilities and infrastructure as well as community income that continues to increase. The potential of the village continues to be explored and planned in carrying out innovative and exploratory development based on Village Regulations. The response of the Village Apparatus and Village Representative Body as well as the village community was quite enthusiastic, very excited, listened and responded in the discussion of techniques for the formation of Village Regulations as an effort to improve the progress of village welfare